2019
DOI: 10.4103/shb.shb_17_19
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and predictive factors of internet addiction and its relationship with emotional intelligence among medical students

Abstract: Introduction: Abundant applications of the Internet in recent years have resulted in emerging of a phenomenon known as "Internet addiction." The present study was conducted with the aim of investigating the prevalence of Internet addiction (IA) and its relationship with emotional intelligence (EI) among students of Qazvin University of Medical Sciences. Methods: The present cross-sectional study was carried out on 325 medical students who were studying at five faculties of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Recent research has shown that an increasing number of Internet users throughout the world are experiencing IA, with notable issues arising among university students (Dehghankar et al, 2019). There are two types of IA, including the generalized and specific.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Recent research has shown that an increasing number of Internet users throughout the world are experiencing IA, with notable issues arising among university students (Dehghankar et al, 2019). There are two types of IA, including the generalized and specific.…”
Section: Review Of Literaturementioning
confidence: 99%
“…18 University students also reported feeling angry, confused, depressed, fatigued, or nervous more easily and becoming more susceptible to get cold due to poor sleep quality; 33% admitted to taking sleeping pills to fall asleep, as well as exhibiting a higher tendency to consume alcohol. 19,20 The literature considers internet addiction (IA) as a major factor affecting university students' sleep quality, 21 but the correlation with FB usage and addiction level among them remains unclear. It is thus necessary to clarify the relationship between FB addiction and sleep quality.…”
Section: Introductionmentioning
confidence: 99%
“… 18 University students also reported feeling angry, confused, depressed, fatigued, or nervous more easily and becoming more susceptible to get cold due to poor sleep quality; 33% admitted to taking sleeping pills to fall asleep, as well as exhibiting a higher tendency to consume alcohol. 19 , 20 …”
Section: Introductionmentioning
confidence: 99%
“…As a result, overuse of social media can lead to a plethora of health issues, such as difficulty sleeping, musculoskeletal discomfort, mood imbalances, and impaired daily functions, as well as addiction-like behavior in a minority of people. 9,10 WhatsApp is a social media application that requires mobile numbers for the registration of its users. It enables direct and instant encrypted messaging between users and the creation of groups to facilitate the sharing of messages -for example, texts, images, voice notes, videos, locations, and files of differing formats.…”
Section: Introductionmentioning
confidence: 99%